Dual Energy X-Ray Transmission Imaging for Concentration and Control of Solids (ABSTRACT PAGE) - T. P. R. de Jong; W. L. Dalmijn; H. U. R. Kattentidt (International Mineral Processing Congress, 2003)
"Research at Delft University aims to develop systems for automatic inspection and sorting of bulk solids which can be applied in the mineral processing and recycling industry. A recent development includes an automatic sorter based on airport X-ray inspection technology. It is designed for continuous inspection and sorting of 5 – 150 mm solids and has as objective a cost effective and high capacity on-line inspection and sorting.Dual energy X-ray transmission imaging provides instantaneous data about particle dimensions and the atomic number distribution. The system provides particle thickness and average atomic number on a pixel level at scanning speeds between 250 and 500 lines / second. With existing X-ray components inspection speeds between 0.5 and 2 m/s at approximately 1-meter inspection width and between 1.5*1.5 and 5*5 mm2 sensor resolution can be achieved.Imaging algorithms that were developed by Delft University for applications in recycling, waste cleaning and other applications acquire shape, size distribution and composition data. Currently on-line processing of a product at a rate of around 200 particles per second is possible using a standard PC. Experiments with a demonstration X-ray unit indicated good potential for various applications in solids processing. They include continuous inspection of organic content, sulphur, chlorine, ash, and metal distribution. It is applicable for coal cleaning, ore sorting, industrial minerals, and various applications within waste cleaning and recycling. Dual energy X-ray transmission fundamentals and recent progress in system development and applications are presented."